(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the use of songs and music as a tool for teaching listening skills, highlighting its benefits for learners of all ages and contexts. It explains why music is effective, emphasizing its ability to capture attention, enhance memory, and promote active listening. The article also provides practical strategies, such as lyric-focused activities, singing along, and genre exploration, to engage learners and improve their listening abilities. It concludes by discussing the broader advantages of using music, including fostering cultural understanding and emotional connection. This resource is valuable for educators, language instructors, and anyone interested in innovative teaching methods.